Litter Dynamics in Fruit Orchards and Natural Forests in the West Coast Region of India – A Comparative Analysis - Uthappa, A.R.; Shishira, D.; Chavan, S.B.; Kumar, Parveen (Indian Forester, 2024)
Litter accumulation and decomposition play a vital role in nutrient cycling, carbon sequestration, and overall ecosystem functioning. This study investigates the dynamics of litter accumulation and decomposition between fruit orchards (Anacardium occidentale and Mangifera indica) and forest ecosystems, focusing on the influence of key environmental factors. Litter accumulation and decomposition varied between the systems. The highest accumulation was in A. occidentale (1882.30 kg ha-1 ) and the least was in the forests (1479.47kg ha-1). Leaf litter decay studies revealed that natural forest litter to be the most labile litter and A. occidentale the most recalcitrant. The decay rate coefficients varied significantly among the species and varied from 0.002 to 0.011. Among three systems the negative exponential decomposition model was the best fit in A. occidentale (r2 = 0.967) followed by M. indica (r2 = 0.679) and natural forest (r2 = 0.418). The litter decomposition rate correlated significantly with various climatic parameters, rainfall quantity and rainy days being the most influential factors. These findings emphasize the intricate and variable nature of litter accumulation and decomposition processes in various systems. Additionally, understanding litter dynamics' role in nutrient cycling and soil health can aid in developing more effective land-use plans and ecosystem management strategies for the fragile Western Ghats.